2014
DOI: 10.1155/2014/521313
|View full text |Cite
|
Sign up to set email alerts
|

Receptors of Hypothalamic-Pituitary-Ovarian-Axis Hormone in Uterine Myomas

Abstract: In this study the expression of GnRH, FSH, LH, ER-α, ER-β, and PR receptors was examined in uterine myomas of women in reproductive and perimenopausal age. In cases of GnRH and tropic hormones a membranous and cytoplasmic immunohistochemical reaction was detected, in cases of ER-α and PR the reaction was located in cell nucleus, and in the case of ER-β it manifested also a cytoplasmic location. In some of the examined cases the expression was detected in endometrium, myocytes, and endothelium of blood vessels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
1
9
0
10
Order By: Relevance
“…These menopause-like symptoms limit applicability to short-term therapy. Prior studies have demonstrated extrahypothalamic presence of GnRH receptors in mammalian reproductive tissues (33,34), and in uterine leiomyoma tissues (18,35). These findings suggest that GnRH-a could be used locally to avoid systemic morbidity.…”
Section: Discussionmentioning
confidence: 78%
“…These menopause-like symptoms limit applicability to short-term therapy. Prior studies have demonstrated extrahypothalamic presence of GnRH receptors in mammalian reproductive tissues (33,34), and in uterine leiomyoma tissues (18,35). These findings suggest that GnRH-a could be used locally to avoid systemic morbidity.…”
Section: Discussionmentioning
confidence: 78%
“…Эффективной стратегией для контроля симптомов миомы и остановки их роста является применение препаратов, содержащих агонисты или антагонисты гонадотропин-рилизинг-гормона (GnRH), которые приводят к блокаде высвобождения гонадотропинов гипофизом [3,21]. Действие этих пептидов может быть связано с их непосредственным влиянием на рецепторы GnRH в матке.…”
Section: применение агонистов или антагонистов гонадотропин-рилизинг-unclassified
“…По данным литературы, к 50 годам примерно у 80% женщин образуется хотя бы один миоматозный узел, а у 15-30% из них появляются тяжелые симптомы, включая обильное маточное кровотечение (ОМК), болевой синдром. Эти проявления иногда могут имитировать или маскировать и злокачественные опухоли [3].…”
unclassified
See 2 more Smart Citations